Magnitudes of households’ carbon footprint in Iskandar Malaysia: Policy implications for sustainable development - Zen, Irina Safitri; Al-Amin, Abul Quasem; Alam, Md Mahmudul; Doberstein, Brent (Elsevier, 2021)
The carbon footprint of households is a significant contribution to global greenhouse gas emissions, accounting for 24% of total emissions. As a result, it is critical to quantify a household’s carbon footprint in order to reduce it over time. One of the best ways to measure carbon emitted from various sectors of the economy, including household daily activities, is to calculate a country’s carbon footprint (CF). This study statistically examined the magnitude of households’ carbon footprints and their relationships with household daily activities and certain socio-economic demographic variables in Malaysia. Results revealed that the average household carbon footprint amounted to 11.76 t-CO2. The average also showed that the primary carbon footprint, 7.02 t-CO2 or 59.69% was higher compared to the secondary carbon footprint which was 4.73 t- CO2 or 40.22% and assessment revealed significant differences among household types. The largest carbon footprint was evident in a medium-high cost urban area, estimated at 20.14 t-CO2, while the carbon footprint found in a rural area was 9.58 t-CO2. In the latter, the primary carbon footprint was almost double the figure of 5.84 t-CO2 (61%) than the secondary carbon footprint of 3.73 t-CO2 (39%). The study reveals a higher carbon footprint in urban areas compared to rural ones depicting the effects of urbanisation and urban sprawl on household lifestyles and carbon footprints. Despite some limitations, the findings of this study will help policymakers design and implement stronger policies that enforce low-carbon activities and energy-saving goods and services in order to reduce urban Malaysia’s carbon footprint dramatically.